Comparative Advantages Analysis: Car Manufacturing in Germany and South Korea - Yan, Bolin (Transactions on Economics, Business and Management Research, 2024)
In Germany and South Korea, both countries have comparable strengths in the automotive manufacturing industry and both have a significant position, contributing greatly to GDP growth, employment, and upstream and downstream industries. This paper analyses the advantages of South Korea and Germany through the Porter’s diamond model, analysing six aspects: factor conditions, demand conditions, related and supporting industries, firm strategy, structure and rivalry, government and chance. The result showed that Germany has invested heavily in research and infrastructure, while South Korea is better in responding flexibly to the world’s turbulent situation and in the field of new energy vehicles.